Logistics Tools during Mergers and Acquisitions - BEREZOVSKIY, Eduard Eduardovich; KIZIM, Anatolii Aleksandrovich; GAYDUK, Vladimir Ivanovich; SEKERIN, Vladimir Dmitrievich (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
The article considers basic areas of mergers and acquisitions (M&A) that are peculiar of modern companies based on logistics tools as auxiliary elements when planning various stages of preparing, carrying out and completing the integration or corporation. On this basis modern understanding of the M&A changes both globally and regionally is formed. The article pays special attention to the control over M&A transactions through the efficient implementation of logistics in intercompany processes of various business structures regardless of the scale and sector. It defines modern trends on accelerating M&A transactions in various areas (financial, industrial, energy) based on the extended tools of generally accepted approaches that make it possible to maximize the synergetic effect.